Reconstruction of Tradition and Religious Imagination in Early Apocryphal Writing - Ališauskas, Vytautas (Literatūra, 2021)
Studies of the Christian apocrypha have paid relatively little attention to the authors’ self-awareness and intentions. The authors of the Apocrypha often impersonate characters of the apostolic generation or write about events that could not have been known to them. This leads to the suspicion that they are deliberately trying to manipulate the reader by directly deceiving him. In contemporary scholarship, apocryphal literature is often described as "forgery". We believe that in many cases this is not an accurate characterisation. The aim of the authors was not manipulation, creating a power relationship of authority with the reader, but the reconstruction of tradition by responding to a new Sitz im Leben. The article emphasises the secondary, derivative character of apocryphal literature. The authors of the Apocrypha were convinced of the veracity of their texts because they systematically relied on sources that were reliable from their point of view: the future canonical gospels, the oral contents, often with folkloric features, theological topoi taken over from the previous generation. This made it possible to attribute their work to the apostles or their companions, since the belief of the time was that the work of the disciples could rightly be attributed to the teacher. It is very likely that some of the works reflect the experience of altered states of consciousness.